Pengaruh Enviromental Social and Governance (ESG), Proporsi Komisaris Independen, dan Thin Capitalization terhadap Agresifitas Pajak: Agresifitas Pajak - Andri Syahputra; Agus Sudiyatmoko; Muhammad Ridwan (Yayasan Kayyis Mulia Jaya, 2026)
This study aims to examine and verify the influence of Environmental, Social, and Governance (ESG) factors, the proportion of independent commissioners, and thin capitalization on tax aggressiveness among energy sector companies listed on the Jakarta Stock Exchange during the 2019–2023 period. The study utilizes a sample of 16 companies listed on the Jakarta Stock Exchange, selected via purposive sampling. Secondary data—specifically the financial statements of the sampled companies—were used for the analysis. The variables examined include Environmental, Social, and Governance (ESG) (X1), the proportion of independent commissioners (X2), thin capitalization (X3), and tax aggressiveness (Y). Data analysis was conducted using EViews 12 software, employing descriptive statistical analysis, model estimation tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination test. The results indicate that, individually, ESG and the proportion of independent commissioners do not significantly affect tax aggressiveness, whereas thin capitalization does have a significant effect. However, when analyzed collectively (simultaneously), ESG, the proportion of independent commissioners, and thin capitalization do significantly influence tax aggressiveness. Keywords: Environmental, Social, and Governance (ESG); Proportion of Independent Commissioners; Thin Capitalization; Tax Aggressiveness